2011
DOI: 10.2147/copd.s16396
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to adherence to chronic obstructive pulmonary disease guidelines by primary care physicians

Abstract: Purpose:Even with the dissemination of several clinical guidelines, chronic obstructive pulmonary disease (COPD) remains underdiagnosed and mismanaged by many primary care physicians (PCPs). The objective of this study was to elucidate barriers to consistent implementation of COPD guidelines.Patients and methods:A cross-sectional study implemented in July 2008 was designed to assess attitudes and barriers to COPD guideline usage.Results:Five hundred US PCPs (309 family medicine physicians, 191 internists) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 20 publications
5
83
1
1
Order By: Relevance
“…Further, the study by Salinas et al39 found that physicians who have difficulty assessing response to therapy were less likely to adhere to recommendations on long-acting bronchodilator use. As suggested by the authors of the study, this may be because long-acting bronchodilators produce subtle but meaningful improvements, which can be difficult for physicians to recognize 39. Moreover, physicians may not recognize a benefit of therapy in individual patients who have infrequent exacerbations, as decreased frequency of exacerbations is an important measure of the efficacy of inhaled therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the study by Salinas et al39 found that physicians who have difficulty assessing response to therapy were less likely to adhere to recommendations on long-acting bronchodilator use. As suggested by the authors of the study, this may be because long-acting bronchodilators produce subtle but meaningful improvements, which can be difficult for physicians to recognize 39. Moreover, physicians may not recognize a benefit of therapy in individual patients who have infrequent exacerbations, as decreased frequency of exacerbations is an important measure of the efficacy of inhaled therapies.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Salinas et al 21 showed that only one of four primary care physicians adhered . 90% of the time to guideline recommendations regarding spirometry or long-acting bronchodilator use.…”
Section: Discussionmentioning
confidence: 99%
“…12 These evidence-based resources are free and easily accessible via the Internet, and many have been recently issued or updated, integrating new scientific findings and reflecting the availability of emerging therapeutic options. 13 One of the barriers for an evidence-based approach to COPD by general practitioners in Mexico is the limited awareness of these guidelines among primary care physicians; in our survey, just 60% of the PCPs responded that they use a clinical guideline for diagnosis and treatment of COPD, with GOLD being the most frequently referenced; 40% of those surveyed did not use a guideline because they were unaware of their existence. Also, almost 13% mentioned that they use the GINA asthma guideline to treat their COPD patients, and some PCPs answered they use the assessment questionnaire CAT as a guideline.…”
Section: Discussionmentioning
confidence: 70%